Mechanistic insights: How nanoparticles modulate plant hormones and defense response signaling under stress - Jasjeet Narang; Bhuvnesh Kapoor; Shakshi Sharma; Navjot Singh Gill (Plant Nano Biology)
Nanotechnology, an interdisciplinary field, explores material properties at the nanoscale (0.1–100 nm), enabling precise control over physical, chemical, and biological characteristics. Nanoparticles (NPs), with their unique size-dependent properties, have revolutionized various fields, including agriculture, where they offer advanced solutions for enhancing plant growth, stress tolerance, and productivity. Over the last decades, NPs have shown promise in modulating phytohormone-mediated processes and molecular signaling pathways, playing pivotal roles in crop improvement and adaptation to environmental challenges. The central role of phytohormones and their cross-talk signaling mechanisms in plant defense serves as an impeccable target for NPs to modulate plant responses. NPs interactions with key signaling mechanisms, such as reactive oxygen species (ROS) involving activation of antioxidative enzymes (e.g., catalase, superoxide dismutase, glutathione peroxidase), and alteration of mRNA expression, contribute to enhanced ability of plants to withstand biotic and abiotic stressors. However, the dose-dependent effects of NPs, ranging from beneficial to phytotoxic, underline the need for careful optimization and regulation. This review delves into the molecular mechanisms underlying NP-plant interactions, highlighting their potential to enhance crop resilience while addressing concerns about their environmental impact. By advancing our understanding of these interactions, this study aims to provide insights into harnessing NPs for sustainable agricultural practices and addressing challenges in global food security.